2010
DOI: 10.1016/j.virol.2009.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cyclophilins involved in different cellular pathways mediate HCV replication

Abstract: Three cyclophilin inhibitors (DEBIO-025, SCY635, and NIM811) are currently in clinical trials for hepatitis C therapy. The mechanism of action of these, however, is not completely understood. There are at least 16 cyclophilins expressed in human cells which are involved in a diverse set of cellular processes. Large-scale siRNA experiments, chemoproteomic assays with cyclophilin binding compounds, and mRNA profiling of HCV replicon containing cells were used to identify the cyclophilins that are instrumental to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 63 publications
6
95
0
Order By: Relevance
“…Spectra were processed with the Bruker TopSpin software package 1.3 and analyzed using the product plane approach developed in our laboratory (43). Backbone assignments were achieved using two-dimensional 1 H, 15 N HSQC and triple resonance three-dimensional 1 H, 15 N, 13 C HNCO, HN(CA)CO, HNCACB, HN(CO)CACB, and HN(CA)NNH spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra were processed with the Bruker TopSpin software package 1.3 and analyzed using the product plane approach developed in our laboratory (43). Backbone assignments were achieved using two-dimensional 1 H, 15 N HSQC and triple resonance three-dimensional 1 H, 15 N, 13 C HNCO, HN(CA)CO, HNCACB, HN(CO)CACB, and HN(CA)NNH spectra.…”
Section: Methodsmentioning
confidence: 99%
“…However, the precise molecular role of the cyclophilins remains to be elucidated. It has been proposed that CypB, CypA, or even Cyp40 is involved (13)(14)(15)(16)(17). However, recently, several laboratories have identified CypA as the key player in the HCV replication (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…We showed that STG-175 has a multi-genotypic activity, exhibits a 13-39 nM EC 50 range among HCV GTs, and does not significantly lose its antiviral activity in the presence of high concentration of human serum. Since we and others showed that host CypA is indispensible for the replication of all HCV GTs [35,[37][38][39][40][41][42], one can speculate that the multi-genotypic activity of STG-175 is due to the fact that it neutralizes the isomerase activity of CypA (Fig 1B).…”
Section: Discussionmentioning
confidence: 82%
“…A difference in the degree of requirement for CypA in the three viral life cycles may also explain the differences in the degree of sensitivity to STG-175 among the three viruses. We and others showed that knocking down CypA by shRNA or siRNA in target cells totally inhibits HCV infection [37][38][40][41] while it partially decreases HIV-1 [66][67][68] and HBV [65] infection. Thus, HCV highly relies on CypA to replicate while HIV-1 and HBV requires CypA to optimally replicate in target cells.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, 19 cyclophilin isoforms with different cellular and tissue distributions have been described (Galat, 2004). Gaither et al (2010) demonstrated that HCV replication relies on several cellular pathways linked to cyclophilins A, H, 40, and E. Cyclosporine A, the cyclophilin inhibitor, was demonstrated to inhibit HCV replication directly, both in vitro and in vivo (Watashi et al, 2003). The finding that cyclosporine A's anti-HCV effect was independent of its immunosuppressive function was promising.…”
Section: Cyclophilin Binding Moleculesmentioning
confidence: 99%